14‐3‐3ɛ/ζ Affects the stability of δ‐catenin and regulates δ‐catenin‐induced dendrogenesis. Issue 1 (29th November 2012) - He, Yongfeng; Han, Jeong Ran; Chang, Ockyoung; Oh, Minsoo; James, Sarah E.; Lu, Qun; Seo, Young-Woo; Kim, Hangun; Kim, Kwonseop
Abstract : Accumulated evidence suggests that aberrant regulation of δ‐catenin leads to pathological consequences such as mental retardation and cognitive dysfunction. This study revealed that 14‐3‐3ɛ/ζ stabilizes δ‐catenin, with different binding regions involved in the interaction. Furthermore, the specific inhibition of the interaction of 14‐3‐3 with δ‐catenin reduced levels of δ‐catenin and significantly impaired the capacity of δ‐catenin to induce dendritic branching in both NIH3T3 fibroblasts and primary hippocampal neurons. However, the S1094A δ‐catenin mutant, which cannot interact with 14‐3‐3ζ, still retained the capability of inducing dendrogenesis. Taken together, these results elucidate the underlying events that regulate the stability of δ‐catenin and δ‐catenin‐induced dendrogenesis.